Design and demonstration of an underwater acoustic carpet cloak - Yafeng Bi (Nature Portfolio, 2017)
Abstract The carpet cloak, which is designed to hide the objects placed on a reflecting surface, has become a topic of considerable interest. Inspired by those theoretical works, the experimental realization of acoustic carpet cloak in air host has been reported. However, due to the difficulty in obtaining the unit cell in reality, the underwater carpet cloak still remains in simulation thus far. Here, we design and fabricate a realizable underwater acoustic carpet cloak. By introducing a scaling factor, the structure of the carpet cloak, which is comprised of layered brass plates, is greatly simplified at the cost of some impedance match. The experimental results demonstrate a good performance of the proposed carpet cloak in a wide frequency range. Our work paves the way for future applications in the practical underwater devices.